Examples
x+y=4x+y=4 , x-y=2x−y=2
Step 1
Multiply each equation by the value that makes the coefficients of xx opposite.
x+y=4x+y=4
(-1)⋅(x-y)=(-1)(2)(−1)⋅(x−y)=(−1)(2)
Step 2
Step 2.1
Simplify the left side.
Step 2.1.1
Simplify (-1)⋅(x-y)(−1)⋅(x−y).
Step 2.1.1.1
Apply the distributive property.
x+y=4x+y=4
-1x-1(-y)=(-1)(2)−1x−1(−y)=(−1)(2)
Step 2.1.1.2
Rewrite -1x−1x as -x−x.
x+y=4x+y=4
-x-1(-y)=(-1)(2)−x−1(−y)=(−1)(2)
Step 2.1.1.3
Multiply -1(-y)−1(−y).
Step 2.1.1.3.1
Multiply -1−1 by -1−1.
x+y=4x+y=4
-x+1y=(-1)(2)−x+1y=(−1)(2)
Step 2.1.1.3.2
Multiply yy by 11.
x+y=4x+y=4
-x+y=(-1)(2)−x+y=(−1)(2)
x+y=4x+y=4
-x+y=(-1)(2)−x+y=(−1)(2)
x+y=4x+y=4
-x+y=(-1)(2)−x+y=(−1)(2)
x+y=4x+y=4
-x+y=(-1)(2)−x+y=(−1)(2)
Step 2.2
Simplify the right side.
Step 2.2.1
Multiply -1−1 by 22.
x+y=4x+y=4
-x+y=-2−x+y=−2
x+y=4x+y=4
-x+y=-2−x+y=−2
x+y=4x+y=4
-x+y=-2−x+y=−2
Step 3
Add the two equations together to eliminate xx from the system.
xx | ++ | yy | == | 44 | |||||
++ | -− | xx | ++ | yy | == | -− | 22 | ||
22 | yy | == | 22 |
Step 4
Step 4.1
Divide each term in 2y=22y=2 by 22.
2y2=222y2=22
Step 4.2
Simplify the left side.
Step 4.2.1
Cancel the common factor of 22.
Step 4.2.1.1
Cancel the common factor.
2y2=22
Step 4.2.1.2
Divide y by 1.
y=22
y=22
y=22
Step 4.3
Simplify the right side.
Step 4.3.1
Divide 2 by 2.
y=1
y=1
y=1
Step 5
Step 5.1
Substitute the value found for y into one of the original equations to solve for x.
x+1=4
Step 5.2
Move all terms not containing x to the right side of the equation.
Step 5.2.1
Subtract 1 from both sides of the equation.
x=4-1
Step 5.2.2
Subtract 1 from 4.
x=3
x=3
x=3
Step 6
The solution to the independent system of equations can be represented as a point.
(3,1)
Step 7
The result can be shown in multiple forms.
Point Form:
(3,1)
Equation Form:
x=3,y=1
Step 8